Rio Conventions Redux: An Argument for Merging the Trio into a Single Convention on Environmental Management - Young, Walker (Consilience, 2010)
It has been argued that the separation of environmental management into three different subject areas - climate change, biological diversity and desertification - with different implementing bodies is not an ideal approach to the Rio Conventions. Specifically, the United Nations (UN) would achieve better results if the three Rio Conventions were consolidated into one Convention on Environmental Management (CEM). This would allow the streamlining of UN organizations into a stronger, consolidated body. Such a unified structure would be more effective in addressing the convention goals, due to its enhanced integration and coordinated assessment and implementation. By consolidating secretariats and moving operations to a single location, the CEM would benefit from enhanced knowledge management and greater efficiency of operations. Further, a systems theory view of environmental management supports an integrated approach that maximizes sustainability by addressing interdependent ecosystem functions in a holistic matter.